Allopurinol-Induced Stevens–Johnson Syndrome in Javanese Men With Positive HLA‐B*58:01 - Ferdiana, Astri; Fachiroh, Jajah; Oktarina, Dyah Ayu Mira; Irwanto, Astrid; Mahendra, Caroline; Febriana, Sri Awalia; Soebono, Hardyanto (Frontiers in Genetics, 2022)
Background Allopurinol is the most commonly used drug for the treatment of gout arthritis. However, the use of allopurinol is associated with severe cutaneous adverse reactions (SCARs), life-threatening immune-mediated reactions that include Stevens–Johnson syndrome (SJS). SJS induced by allopurinol has been strongly linked with the presence of HLA-B *58:01 in Asian population. Such study has not been conducted in Indonesia. Case description We present two cases with clinical diagnosis of SJS. These patients had Javanese ethnicity, for which evidence on the genetic predisposition of allopurinol-induced SJS/TEN had not been established. Testing for HLA-B∗5801 was positive in both cases. Conclusion Our case report confirmed findings from studies in Asian countries that linked HLA-B∗5801 and allopurinol-induced SJS/TEN. Larger study is needed to elicit evidence that HLA-B∗58:01 can potentially be used as a genetic marker for allopurinol-induced SCARs among different ethnicities in Indonesia.